The use of robotics applications in classrooms with students with cerebral palsy - Gonçalves, Marcus Fabiano; Oliveira, Terezinha Azevedo de (Seven Editora, 2024)
In this article, we sought to raise the needs of students with cerebral palsy and their restrictions in the face of the school assistance that is guaranteed to them under the Federal Constitution for a dignified life. It is discussed how these students are assisted in the school environment, whether there is adequate structure and equipment necessary for their development in an egalitarian and dignified way. To this end, the present study will be supported by a bibliographic reference on the theme to analyze the distancing opened by the unequal circumstances produced in the school context by factors such as: the lack of auxiliary equipment for learning, such as, for example, the use of robotics. Although the Public Prosecutor's Office of the State of Rondônia (MPE/RO), when called upon, has met this demand at times, there is still much to be done. In this study, a parallel will also be made to the inequalities found in Brazil in a comparative analysis with another country, such as India, to verify if there are other underlying issues and what they are. In this context, we will try to note whether Brazilian representative democracy only guarantees equality and formal freedom in the areas of politics and justice – from where they coexist with inequalities, thus hiding a disguised colonialism, to deduce other possible ways to achieve possible concrete solutions and the correction of these inequalities in the educational context. DOI:https://doi.org/10.56238/sevened2024.007-007